Building physical activity and sedentary behavior support into care for youth with type 1 diabetes: patient, parent and diabetes professional perceptions. Issue 2 (5th December 2014) - MacMillan, Freya; Kirk, Alison; Mutrie, Nanette; Moola, Fiona; Robertson, Kenneth
Abstract : Objective: To explore stakeholder's perceptions of physical activity (PA) and sedentary behaviour support in youth with type 1 diabetes (T1D), to aid intervention development. Methods: Primary data were collected between February and September 2012. Patients (N = 16), parents (N = 16), and professionals (N = 9) were recruited from a diabetes clinic for a qualitative study. Semi‐structured interviews (N = 33) and focus groups (N = 2), using broad open‐ended questions, were conducted in patient's/parent's homes, and at the diabetes clinic. Data were analysed thematically. Results: Based on participants' experiences and interpretations, parent and peer support were perceived as essential. Professionals identified they could do more to encourage PA. Technology and information on local opportunities, in addition to in‐person support, and a combination of group and one‐to‐one support were perceived as useful. Important perceived components of support were: diabetes preparation, management and support; enjoyment; education; and incorporation of behaviour change techniques. The time of diagnosis was described as an appropriate point to initiate interventions. Conclusions: The findings will help the development of future PA and sedentary behaviour interventions for youth with T1D.